The Use of English UKBM to Support Independent Learning in Senior High School (RETAIN, 2020)
In the educational setting, UKBM, defined as a learning unit that is organized in sequence from easy to difficult based on the basic competencies, has to be used by schools that implement Semester Credit System. By using UKBM, one of the benefits for learners is being independent in learning and achieving the competencies. However, in learning English, most EFL learners think that English is difficult. Hence, if EFL learners learn English independently through UKBM, English teachers need to design the process of learning through UKBM as interactive as possible in order to make the EFL learners have willing to learn and foster independent learning. Thus, the present study attempted to (1) describe how an English teacher uses UKBM to support independent learning activity (2) find out EFL learners’ perceptions toward independent learning through UKBM, and (3) describe how EFL learners optimize independent learning through UKBM. This study was conducted in one of favorite senior high schools in Sidoarjo and was employed a mixed-method study in the form of an embedded research design. The data were collected through (1) observation to describe how an English teacher uses UKBM to support independent learning activity (2) questionnaire to find out EFL learners’ perceptions toward independent learning through UKBM, and (3) interview to describe how EFL learners optimize independent learning through UKBM. The result showed that the English teacher has not effectively and optimally used the UKBM to support independent learning since the English teacher still implemented the classical learning model in teaching the EFL learners. Next, the majority of the EFL learners had a more positive perception toward general independent learning than independent learning through UKBM. However, in terms of the usage of UKBM for independent learning, most of the EFL learners perceived it positively. Last, the EFL learners still tried to optimize independent learning through UKBM by nine ways those were knowing the purposes of learning to always keep the spirit in learning, building the intention to get knowledge in learning English, having motivation in learning, finding the best ways or strategies in learning, managing time properly, comprehending the materials, exploring other sources, making a group for studying, and avoiding relying on friends.